Quartz‐containing glass‐ceramics in the SiO2–Li2O–K2O–MgO–CaO–Al2O3–P2O5 system. (3rd January 2019) - Rampf, Markus; Fisch, Martin; Helsch, Gundula; Deubener, Joachim; Ritzberger, Christian; Höland, Wolfram; Dittmer, Marc
Abstract: Volume crystallization of quartz, triggered by adding P2 O5, was investigated in the multicomponent SiO2 –Li2 O–K2 O–MgO–CaO–Al2 O3 –P2 O5 glass system. Glass‐ceramics comprising quartz as the main crystal phase besides lithium disilicate (Li2 Si2 O5 ) as a minor crystal phase were produced by controlled crystallization from the parent glass. According to quantitative crystal phase analysis by means of Rietveld refinement the mass fraction of the minor Li2 Si2 O5 phase decreased with increasing P2 O5 content, while the fraction of quartz increased. Scanning electron microscopy revealed lath‐like Li2 Si2 O5 embedded in a matrix of rather globular quartz crystals forming an interlocking microstructure. Well machinable glass‐ceramics with a mean biaxial flexural strength of about 300 MPa and a fracture toughness of about 2.0 MPa × m 0.5 could be realized. With mean values ≥13.6 × 10 −6 K −1 the glass‐ceramics coefficient of thermal expansion is close to the one reported for low‐quartz crystals. The ease of production based on conventional glass melting and fabrication technology together with the good mechanical, optical, and machining properties enables the application of these materials in prosthodontics.